Learning from Chinese Management - Isac, Florin Lucian; Remeș , Eugen Florin (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
China is one of the fastest-growing economies and has gained a leading position in terms of production or exports. China’s managerial and business practices are influenced by its traditional cultural values. The article investigates, along with the influences of these values on management, the points of interest of the Chinese management model for other cultures.